P120 catenin expression and its correlation with E-cadherin in salivary gland neoplasms - Ekarat Phattarataratip; Nicha Kositkittiwanit; Pruch Kajornkiatkul; Pataraporn Yeunyong; Ratanatip Ratanapitak (Journal of Oral Biology and Craniofacial Research)
Objectives: Altered P120 catenin expression has been associated with E-cadherin loss and poor prognosis in several cancers. The objectives of this study were to examine the P120 catenin expression in salivary gland neoplasms in correlation with E-cadherin and assess the relationships between their expression levels and pathologic characteristics. Methods: Fifty-two cases of salivary gland neoplasms, i.e. 25 mucoepidermoid carcinomas (MEC), 13 adenoid cystic carcinomas (ACC), 12 pleomorphic adenomas (PA) and 2 polymorphous adenocarcinomas (PAC) were included. The expression of P120 catenin and E-cadherin was investigated immunohistochemically. Results: Both P120 catenin and E-cadherin were overexpressed in salivary gland neoplasms, compared to normal tissue. P120 catenin was primarily detected on the membrane of neoplastic cells in most cases. A significant correlation between levels of expression of both proteins was noted in MECs. In ACCs and PA, ductal cells showed positive immunoreactivity, whereas myoepithelial cells variably expressed both proteins. Increased P120 catenin expression was significantly associated with the solid subtype of ACCs. Conclusions: The cadherin-catenin complex is preserved in the heterogenous tumor cell population in salivary gland neoplasms. Overexpression of P120 catenin may be involved in the progression to solid ACCs.